Demographic Determinants of Rural Labour Resources in Poland - Kowaleski, Jerzy; Majdzińska, Anna (Olsztyn Economic Journal, 2018)
The article discusses the state and age structure of the subpopulation comprising the potential labour force in Polish voivodeships and counties, particularly in their rural areas, between 2002 and 2030. It also shows how the balance of the potential labour force changed as a result of the inflow of birth cohorts at early-working age and the outflow of people at pre-retirement and early retirement age. The analysis additionally takes account of selected social characteristics of the population such as education and health. The necessary statistical data were sourced from the publications of the Central Statistical Office.